Magnetic susceptibility of p-Si(B) single crystals grown in "vacancy" regime at presence of thermodonors created by thermal treatments at 450 °C - Babych, V.M.; Luchkevych, M.M.; Pavlovskyy, Yu.V.; Tsmots, V.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2008)
By using the Faraday method and complex of electro-physical studies (Hall effect, ESR, etc.) the features of magnetic susceptibility (χ) of p-Si(B) crystals grown in “vacancy” regime and annealed at 450 °C are studied. It is demonstrated that the presence of deep thermodonors with the ionization energy Еі ≥ 200 meV in these samples contributes to the appearance of a paramagnetic constituent with the magnetic susceptibility (χ par) even at 300 K. χ par in this material does not depend on temperature in the range of 77 - 300 K that can testify on the Van-Fleck origin of this magnetic susceptibility component. Absence of nonlinearities in the dependence χ(H) within the interval 0.3-4 kOe shows uncooperative character of magnetism found out.